Forecasting potato yield dynamics in the Tashkent region of the Republic of Uzbekistan - Vakhabov V. V.; Hidoyatova M. A. (E3S Web of Conferences, 2023)
Observations of some phenomenon, the nature of which changes over time, generates an ordered sequence, which is called a time series. The statistical regularity of the series of dynamics ȳt the average potato yield in the Tashkent region of the Republic of Uzbekistan (based on the materials of the CSO of the Republic of Uzbekistan for 2000-2018 year) was studied by the method of statistical analysis of time series. Point and interval estimates for the average potato yield were built with a 95% guarantee, explicit types of trends were identified and the yield in the Tashkent region was predicted for subsequent years. Using the Darbin-Watson statistical criteria, it was found that the average potato yield in the region has autocorrelation dependence.